Echo voltage reflected by turtle on various angles - Sunardi Sunardi; Anton Yudhana; Azrul Mahfurdz; Sharipah Salwa Mohamed (Universitas Ahmad Dahlan, 2015)
This research proposes the acoustic measurement by using echo sounder for green turtle detection of 1 year, 12 and 18 years. Various positions or angles of turtles are head, tail, shell, lung, left and right side. MATLAB software and echo sounder are used to analyse the frequency and the response of the turtle as echo voltage and target strength parameter. Based on the experiment and analysis have been conducted, the bigger size of the turtle, the higher echo voltage and target strength. The target strength of turtle for lung and shell for all ages are -26.52 dB and –26.17 dB respectively. The target strength of turtles in this research is different with target strength of fish in our previous research. Therefore, for future research, the repellant system based on differences of target strength the turtle and fish for avoided the turtle trapping in the net can be implemented to protect the population of turtle from extinction